Potentials of biosurfactant and biomass from locally isolated panus tigrinus and klebsiella pneumonia strains and decolorization of selected industrials dye - Jamal, Parveen; Monawar, Munajid; Al-Khatib, Ma'an Fahmi Rashid (Journal of Pure and Applied Microbiology, 2014)
Pollution problem posed by dye contamination, resulting from errant human technological activities has for long posed a challenge for researchers. Biosorption is becoming a promising alternative to replace or supplement the present dye removal processes, which are used for removing dyes from wastewater. In this study, the removal of four dyes; Congo Red, Malachite Green, Neutral Red and Reactive Blue 19,by biosorption using biomass of fungus and bacteria, panustigrinus, klebsiellapneumoniae were investigated. Bacterial biosurfactant, obtained from klebsiella pneumonia, was also tested for dye removal. Fungal biomass proved to be the best remover amongst the three bioactive biosurfactant and biomass, which removed 96.948% of Congo Redfollowed by 89.231% removal of Reactive Blue 19.